Dynamic customisation, validation and integration of product data models using semantic web tools. (1st January 2014) - Krima, Sylvere; Feeney, Allison Barnard; Foufou, Sebti
Standard product data models enable information exchange across different organisations, actors, processes and stages in the product lifecycle. These standard models need to support diverse domain-specific requirements from the multitude of disciplines involved during a product's lifecycle. Due to this diversity, challenges are to: 1) develop multidisciplinary models; 2) extend them to support new requirements over time; 3) implement the resulting gigantic information models. ISO 10303, the reference standard for PLM-related data models provides mechanisms to enable specialisation of generic product data to address some of these challenges. In this paper, we introduce the need for dynamic product data models, detail the ISO method and identify its limitations. We present enhancements to that methodology using ontologies and the SPARQL Inference Notation (SPIN) for validating product data. To conclude, we show how these ontologies can be leveraged to ease and strengthen PLM data integration through the use of Linked Data.